Development Of Literacy In Al Iman Islamic Elementary School - Wiranto, Eko Prasetyo Nurbudi (Prosiding University Research Colloquium, 2021)
This research aims to find out the development of literacy in elementary school students, especially in Integrated Islamic Elementary School Al Iman Magelang in the even semester of the 2020/2021 school year. The approach in this study is qualitative research with descriptive methods, while the data retrieval process uses interview and observation techniques. The subjects of the study were principals, students, teachers, and school library officers. Data analysis is done by reducing the data that has been collected. Data is processed by taking a qualitative approach to answering research questions. Based on research that has been done, the development of children’s literacy at Al Iman Magelang Integrated Islamic Elementary School is managed by the library in collaboration with classroom teachers, extras and parents. Literacy development is carried out during the learning process and supported by extracurricular activities. The activities carried out to support literacy include reading 15 minutes before learning, retelling readings that have been read at home, reading corners in the classroom, literacy competitions, visits to regional libraries and so on. Special attention is given to students who are low in literacy skills by providing opportunities to represent the classroom in the literacy race, this is done so that confidence in children can be grown.